Respon Pertumbuhan dan Produksi Tanaman Gambas (Luffa acutangula L.) Dengan Pupuk Organik Cair Limbah Industri Tempe Dan Kompos Kulit Bawang Merah - Gawati Harita; Ellen Panggabean; Abdul Rahman (Universitas Medan Area, 2022)
Gambas (Luffa acutangula, L.) is an annual vegetable plant belonging to the fruit vegetable group originating from India, but has adapted well in Southeast Asia including Indonesia. This study aims to determine the effect of liquid organic fertilizer application from tempe industrial waste and application of onion peel compost on the growth and production of gambas. This research method uses a factorial randomized block design (RAK) which consists of 2 factors, namely: application of liquid organic fertilizer from tempe industrial waste and onion skin compost. The provision of liquid organic fertilizer for tempe industrial waste consists of 4 levels of treatment, namely: B0 = control/without treatment, B1 = Liquid Organic Fertilizer 22 ml/L, B2 = Liquid Organic Fertilizer 44 ml/L, B3 = Liquid Organic Fertilizer 66 ml/L L. The second factor of onion peel compost consisted of 4 levels of treatment, namely: P0 = Control/without treatment, P1 = Shallot Skin Compost 10 tons/ha (1.2 kg), P2 = Shallot Compost 20 tons/ha (2 ,4 kg), P3 = Compost of Shallot Skin 30 tons/ha (3.6 kg). Observation variables included: plant length (cm), number of leaves (strands), fruit diameter per sample plant (cm), fruit length from sample plant (cm), fruit weight per sample plant (g), fruit weight per plot (g), number of fruits per plot (g). The results showed that the combination of liquid organic fertilizer from tempe industrial waste and onion peel compost had a significant effect on plant length and fruit weight per sample plant, but had no significant effect on leaf number, fruit diameter, fruit length, fruit weight per plot and number of fruits per plot.